Migration, Balik-Islam, and Identity Formation of Muslims in Palawan of The Philippines - Mufahamah, Raisatul; Sujadi, Sujadi; Conceição Savio, Edegar da (Pascasarjana IAIN Pontianak, 2025)
Since the 1970s, Muslims in Mindanao, Philippines have had a conflict with the government. The religious-based conflict not only caused deaths but also forced people to migrate from Mindanao. One of the targeted places was Palawan Island. It is situated in the southwest of the Philippines – rather far from any other islands in the Philippines. It is then called “The Last Frontier”. This research focuses on studying the reasons for their migration to Palawan, Philippines and keeping their Islamic identities from 1970 to 2001. This research uses a socio-historical and socio-anthropological approaches. Survey methods and structured interviews are utilized to complete the literature study as primary or secondary sources. The theory of migration conflict from Nancie L. Gonzalez is used to analyse the migration in Palawan whereas for the analysis of the identity establishment, the theory of collective identity is utilized. As a result, the migration of the Muslims of Palawan, Philippines in 1970-2001 was a complex and recurrent event. The motive of the migration was the conflict in Mindanao resulting in economic opportunities in Palawan. As for the identity establishment, building the mosque became a symbol and a starting point for the Muslim migrant in Palawan. They had shared meaning in the phenomenon of Balik-Islam and their sense of belonging to Palawan as an Autonomous Region Muslim Mindanao (ARMM) via plebiscite–referendum for integration into Muslim Mindanao or not.